Erythema nodosum leprosum in a treatment-naïve patient: clinical clues not to miss in primary care - Samsudin, Suhaiza; Hamzah, Fatihah (Universiti Kuala Lumpur, 2025)
Leprosy is known as a “great mimicker” due to its broad spectrum of clinical presentations. Erythema nodosum leprosum (ENL), a Type 2 lepra reaction, typically manifests as acute, painful erythematous nodules during or after initiation of multidrug therapy (MDT) in multibacillary patients. We report a case of a 66-year-old treatment-naïve man who presented to primary care with chronic and painless nodules in the absence of classical lepromatous features or prior therapy. Slit-skin smear (SSS) confirmed multibacillary leprosy with a moderate bacterial index (BI) and an inactive morphological index (MI), supporting the diagnosis of chronic ENL. The patient responded well to a second-line MDT regimen and corticosteroids. This case highlights an unusual presentation of ENL preceding treatment and underscores the diagnostic challenges faced in primary care, particularly when classical signs of leprosy are absent. We discuss key differential diagnoses and the importance of early recognition to avoid misdiagnosis and prevent complications.